A contemporary review of venous adventitial cystic disease and three case reports. (February 2015) - Chen, YueXin; Sun, RuiXue; Shao, Jiang; Li, YongJun; Liu, ChangWei
Venous adventitial cystic disease is a rare vascular disease. The objective of the study is to contemporarily review the literature of venous adventitial cystic disease and report three other new cases of adventitial cystic disease in common femoral vein. Articles published between 1947 and April 2013 were searched in OVID and PubMed databases. The search yielded only 38 reported cases of venous adventitial cystic disease. The general characteristics and disease management information of the 41 cases (including our current 3 cases) were analyzed. Venous adventitial cystic disease could develop late in life with an average age of 48.39 years (range, 5 to 77 years). Similar to arterial adventitial cystic disease, venous adventitial cystic disease was also found to have a male predominance (male to female ratio, 1.28:1). The common femoral vein was the most likely vein to be involved (65.9%, 27 cases). Right and left sides were almost equally affected. Extremity swelling (86.8%, 33 cases) was the main symptom of patients presenting with venous adventitial cystic disease. Excision of cyst wall in 30 patients (73.2%) was the main surgical procedure with a recurrence rate of 11.5%. Thirteen involved veins were resected; of which, 10 were reconstructed with prosthetic or autologous graft. No recurrence was reported in these 13 patients. Postoperatively, nine cases received an anticoagulation therapy. In conclusion, the etiology, treatment strategy, and outcomes of venous adventitial cystic disease could not be well understood in the present review due to limited numbers of cases. Studies with careful follow-up for at least up to first several months are recommended.